2009
DOI: 10.1002/btpr.153
|View full text |Cite
|
Sign up to set email alerts
|

Access of cellulase to cellulose and lignin for poplar solids produced by leading pretreatment technologies

Abstract: Adsorption of cellulase on solids resulting from pretreatment of poplar wood by ammonia fiber expansion (AFEX), ammonia recycled percolation (ARP), controlled pH, dilute acid (DA), flowthrough (FT), lime, and sulfur dioxide (SO(2)) and pure Avicel glucan was measured at 4 degrees C, as were adsorption and desorption of cellulase and adsorption of beta-glucosidase for lignin left after enzymatic digestion of the solids from these pretreatments. From this, Langmuir adsorption parameters, cellulose accessibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
123
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 94 publications
12
123
1
2
Order By: Relevance
“…The greater cellulose accessibility for AFEX pretreated solids suggests that disruption of lignincarbohydrates linkages plays a greater role in enhancing accessibility than xylan/lignin removal. However, consistent with another finding (Kumar and Wyman, 2009b), the data here for selective lignin removal supports the hypothesis that lignin controls xylan accessibility, which consequently does not have a major impact on cellulase adsorption. The high cellulose accessibility for AFEX and lime pretreated solids could account for their good glucose release reported in the literature at cellulase loadings of 15 and 60 FPU (Wyman et al, 2005a).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The greater cellulose accessibility for AFEX pretreated solids suggests that disruption of lignincarbohydrates linkages plays a greater role in enhancing accessibility than xylan/lignin removal. However, consistent with another finding (Kumar and Wyman, 2009b), the data here for selective lignin removal supports the hypothesis that lignin controls xylan accessibility, which consequently does not have a major impact on cellulase adsorption. The high cellulose accessibility for AFEX and lime pretreated solids could account for their good glucose release reported in the literature at cellulase loadings of 15 and 60 FPU (Wyman et al, 2005a).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with the findings here, another study (Kumar and Wyman, 2009b) showed that delignification of solids with a xylan content of <3% resulting from pretreatments at lower pH with dilute acid and SO 2 had a negligible impact on glucose release. On the other hand, delignification of solids produced by high pH pretreatments, such as AFEX and ARP, that contained a significant amount of xylan enhanced glucose release.…”
Section: Impact Of Lignin On Cellulose Accessibilitysupporting
confidence: 91%
See 1 more Smart Citation
“…In previous studies, it was observed that the lignin content is correlated with cellulose accessibility, being a barrier to the enzymatic hydrolysis, by blocking the accessibility of the enzymes to the cellulose microfibrils 12,13 . Lignin also tends to irreversibly bind the enzymes through hydrophobic interactions causing a loss in cellulases activities 14,15,16 .In addition, during the pretreatment step lignin suffer changes in its structure and the effects on the enzymatic hydrolysis of cellulose are not completely understood 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Minimal cellulase loading that allows sufficient binding to cellulose substrate is a goal that some have begun to study (Klein-Marcuschamer et al 2012). An optimum temperature for adsorption has been explored with conflicting results (Kumar and Wyman 2009). To minimize production of glucose in the enzyme bath, small bath volumes and optimum temperature were evaluated.…”
Section: Introductionmentioning
confidence: 99%